2021
DOI: 10.1057/s41287-021-00413-0
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding the Aspirations of Farming Communities in Developing Countries: A Systematic Review of the Literature

Abstract: This study surveys the panorama of research on the importance of aspirations of farming communities, identifies research gaps and prospects for future research. The analysis of 22 studies identified from 419 research articles sheds light on the relationships between aspirations, agriculture, women’s empowerment, poverty, and rural youth. Aspirations of the rural poor play a significant role in shaping their activities and investments. Furthermore, the poor and those who are exposed to natural disasters are mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Local social support networks were crucial in the immediate and medium‐term response to Maria; people moving away has the potential to disrupt them and the structural functioning of the community. While young people leaving rural areas for the reason of employment is not a new phenomenon (see, for example, Glendinning et al, 2003; Trimble and Johnson, 2013; Nandi and Nedumaran, 2021), the aspirations reported by community members illustrate that many entail young people staying and working within the community to build better lives for everyone—this perspective is also evident in other rural areas (see, for example, Giuliani et al, 2017). Some of the NEP placements actively undermined relational well‐being, as well as physical health and material wealth.…”
Section: Discussion: Resilience and Well‐being Following Hurricane Mariamentioning
confidence: 99%
“…Local social support networks were crucial in the immediate and medium‐term response to Maria; people moving away has the potential to disrupt them and the structural functioning of the community. While young people leaving rural areas for the reason of employment is not a new phenomenon (see, for example, Glendinning et al, 2003; Trimble and Johnson, 2013; Nandi and Nedumaran, 2021), the aspirations reported by community members illustrate that many entail young people staying and working within the community to build better lives for everyone—this perspective is also evident in other rural areas (see, for example, Giuliani et al, 2017). Some of the NEP placements actively undermined relational well‐being, as well as physical health and material wealth.…”
Section: Discussion: Resilience and Well‐being Following Hurricane Mariamentioning
confidence: 99%
“…Tabe Ojong et al and Nandi and Nedumaran (2021) concur that the index is a useful tool that is easily integrated into standard surveys. However, in the context of this Special Issue, we would consider such an index as a measure of ambition rather than of aspiration.…”
Section: Aspirations For Future Livesmentioning
confidence: 94%
“…Across the contributions of this Special Issue and their various methodological and disciplinary entry points, all levels of this interplay between local individual aspirations (Mausch et al 2021;Tabe-Ojong et al 2021;Nandi and Nedumaran 2021;Aring et al 2021;La Rue et al 2021 andCrossland et al 2021) and political aspirations (Matejcek and Verne 2021;Müller-Mahn et al 2021;Kalvelage et al 2021;Greiner et al 2021;Höllermann et al 2021;Chamberlin et al 2021) are investigated with a recognition of the influence of considerations at the other end of the spectrum (see Fig. 1).…”
Section: Conceptual Approachmentioning
confidence: 99%
“…The link between resilience and empowerment has been established by various studies, especially in community psychology studies; Lloret et al [21] systematically reviewed 490 studies published from 2019 to 2020 and reported that community training on resilience had empowered parents to increase the prevention of substance abuse in the family. Similarly, a meta-analysis of 419 studies has shown consistent reporting of the significant link between empowerment and resilience among poor rural farmers communities [22].…”
Section: Introductionmentioning
confidence: 91%